2020
DOI: 10.1177/1129729819901223
|View full text |Cite
|
Sign up to set email alerts
|

The effect of angioplasty of single arteriovenous fistula–associated stenosis on arteriovenous fistula blood flow rate

Abstract: Introduction: Percutaneous balloon angioplasty of arteriovenous fistula–associated stenosis is performed for a variety of indications. Successful percutaneous transluminal angioplasty (PTA) is expected to increase in arteriovenous fistula blood flow rate (Qa). A validated approach to predicting changes in Qa based upon stenosis characteristics is not available. Methods: Three baseline parameters were determined in a group of patients with a single arteriovenous fistula–associated stenosis undergoing PTA. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…The stenosis MLD was calculated as previously described. 13 The estimation of stenosis and diameter were performed at the time of the procedure by the operator. These measurements were derived using the angioplasty balloon length and diameter as the reference metric.…”
Section: Angioplasty and Procedural Characteristicsmentioning
confidence: 99%
“…The stenosis MLD was calculated as previously described. 13 The estimation of stenosis and diameter were performed at the time of the procedure by the operator. These measurements were derived using the angioplasty balloon length and diameter as the reference metric.…”
Section: Angioplasty and Procedural Characteristicsmentioning
confidence: 99%
“…[18] Another study reported that both vascular access flow volume and cardiac output were increased by PTA in most cases, whereas in some cases, the cardiac output decreased despite an increase in vascular access flow volume. [19] Beyond its association with cardiac output, baseline VABF serves as the most reliable predictor for changes in VABF [20] The diversity in study characteristics and variations in methodologies and temporal parameters for measuring VABF and cardiac output make it challenging to draw definitive conclusions. Regardless of whether cardiac output increased after PTA, these studies and our findings suggest the necessity of shifting the perspective from the physiological response of the vascular circuit to localized microvascular dysfunction to investigate progressive increases in vascular access flow after PTA.…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis minimum luminal diameter cutoffs of ≤ 2.0 and > 4.5 mm are valuable in forecasting the extent of changes in VABF. [20] The diversity in study characteristics and variations in methodologies and temporal parameters for measuring VABF and cardiac output make it challenging to draw definitive conclusions. Regardless of whether cardiac output increased after PTA, these studies and our findings suggest the necessity of shifting the perspective from the physiological response of the vascular circuit to localized microvascular dysfunction to investigate progressive increases in vascular access flow after PTA.…”
Section: Discussionmentioning
confidence: 99%
“…In the report by Nassar et al, MLD ≤2 mm and ˃4.5 mm before PTA were associated with an increase in VF after PTA of ≥300 mL/min and <300 mL/min, respectively. They reported that stenosis MLD ≤2.0 and >4.5 mm were useful in predicting the magnitude of changes in VF (17). In another similar report, MLD was reported to have a weak positive correlation with VF, but an MLD cutoff of ≤2.5 mm had a good predictive value in detecting VF <500 mL/min (18).…”
Section: Discussionmentioning
confidence: 99%